Pobre galego?: Ideia e representação dos emigrantes galegos na literatura de viagens em Portugal de oitocentos - Resende, Nuno (2018)
The present article aims to question, analyze and interpret literary sources, namely the travel literature, as a contribution to the reconstitution of social types with the discipline of History of Art. We use as a case study, the Galicians, noticed and documented throughout the 20th century by the Portuguese writers. Does this figure, image or identity correspond to what foreigners visiting Portugal during the same century construct with their written and visual reports and records? To answer this question, we propose to focus on descriptions that can contribute to the construction of an «iconography of identity» of this social group that immigration has led to our country in successive waves and generations during the XIXth century.